Structure and properties of hypereutectoid steels in heat-treated state. (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
Our present research is aimed at improving the structure and enhancing the properties of carbon steel of the hypereutectoid composition with a 1.0 - 2.0 % carbon content, modified with cerium or boron for the production of mill rolls. The research was carried out on subproducts obtained by the method of stationary casting in earthen and metal molds. Comparative studies were conducted on 9 versions of smelting before and aftermodification, which were subjected to annealing in three different modes.It has been established that the requirements for the material rolling tool materials are determined by the area of their use. Hypereutectoid steel rolls are characterized by a rather high viscosity and a low wear resistance. This drawback is to some extent eliminated by replacing such steels with eutectoid steels. Viscosity can be increased by heat treatment, Технічний сервіс агропромислового, лісового та транспортного комплексів Technical service of agriculture, forestry and transport №24’ 2024 27 which ensures the formation of a granular structure of pearlite with a corresponding increase in wear resistance by 2-4 times as compared to alloyed eutectoid steel rolls with separate cementite allocations at the grain boundaries. As we show in our present study, the proposed heat treatment modes allow one to ensure an even higher level of properties than in low-alloy steel rolls.
Keywords: hypereutectoid steel; heat treatment; level of properties; structure; mill rolls